Missing jewels - LeBlanc, Hayley (Naperville, Illinois Sourcebooks Young Readers, an imprint of Sourcebooks, 2022)
"Things are going great for Hayley on the set of the mystery show Sadie Solves It. But one day, things start disappearing from the studio--expensive jewelry used on the show, and even earrings from someone's purse! Who's the thief stalking Silver Screen Studios? Hayley doesn't want to get involved... after all, she only plays a detective on TV. But then one of the stolen items is found in her trailer, and her favorite makeup artist, Vee, is blamed for the theft! With the help of her two best friends and co-stars, Hayley begins to investigate. Can they find the real thief before Vee is fired for good?" -- Publisher marketing.
112396
Keywords: Child actors -- Juvenile fiction; Motion picture studios -- Juvenile fiction; Theft -- Juvenile fiction; Detective and mystery stories -- Juvenile literature; Detective and mystery stories; Children's stories; Fiction; Juvenile works